Green Action sebagai Upaya Rehabilitasi Ekosistem Mangrove di Kelurahan Romokalisari, Surabaya - Alwi, Alwi Sina Khaqiqi; Rahayuningsih, Siti; Al Hazman, Muhammad; Widyastuti, Indri ika; Sholikah, Evi Nafiatus; Gastriani, Ovi Prina; Wibowo, Sekarsari; Nisazarifa, Adristi; Pujiputra, Anggarjuna Puncak; Sukarno, Friska Intan; Brian, Thomas; Parman (Jurnal Cakrawala Maritim, 2025)
Mangroves have several functions, including maintaining biological balance in coastal ecosystems and tourism. On the other hand, mangroves are also very vulnerable to natural disturbances, anthropogenic, land conversion, and even pollution from various human activities. The success of mangrove planting activities does not only depend on the selection of the type of mangrove to be planted, but also on the selection of a suitable location to support its growth. Mangroves in Romokalisari Village, Surabaya are currently still relatively few. This needs to be planted because the mangroves function as wave breakers and tourist attractions. Mangrove planting activities in Romokalisari Village, Surabaya, were carried out by residents, lecturers and students of the Surabaya State Polytechnic of Shipping. The results of the mangrove planting are expected to have a positive impact on Romokalisari Village, Surabaya and its surroundings.